REALIZATION OF FEDERAL AND REGIONAL PROGRAMS OF INFERTILITY TREATMENT - N. V. Protopopova; Y. V. Mylnicova; E. B. Druzhinina; E. V. Odareeva (Acta Biomedica Scientifica, 2012)
High frequency of infertility in the Irkutsk region (18—20 %) sharply limits population reproduction. Tubo-peritoneal factor (97,3 %), man's infertility (20 %) are leading factors of infertility in Irkutsk region. It predisposes wide using of IVF as the main way of reproductive problems solution in population. Efficiency of IVF programs depends on such factors as age of patients; duration and causes of infertility.